Structure of Plants across Habitat Types in Amurum Forest Reserve, Plateau State Nigeria - N. Janfa; M.J. Francis; C. Kambai; M.S. Chomini; S.A. Popoola; M. Ukwadi; C.J. Ukanyirioha; T.A. Erhabor; Y.E. Sadiku; J.A. Imoh (Journal of Applied Sciences and Environmental Management, 2021)
The Amurum Forest Reserve is one of the nature reserves in Plateau State North central Nigeria. Strict Nature reserve is prominent among the methods for in situ conservation of biodiversity in Nigeria and also the world at large. A study was conducted in the Forest across three habitat types in order to measure tree height and diameter at breast height (dbh) of trees. 50m x 50m plots were marked across the habitat types by simple random sampling technique. Trees and shrubs were identified to species level. Measurement were limited to all woody plants with diameter at breast height (dbh) of ≥ 10cm. Data collected was analyzed in excel. A total of 397 woody species were identified during the study period. 87.7 of the plants were shrubs while 12.3% were trees. The gallery forest had the highest diameter class(30-35cm) followed by the savanna(25-30cm) and lastly the rocky outcrop with the diameter class of 20-25cm.The rocky outcrop had the highest number of trees with the lowest dbh (10-15cm) while the gallery forest had more trees in the highest diameter class (30-35) (Figure 2). The highest mean height distribution in the Gallery forest shows that the plant communities in this habitat type has grown over the years without disturbance since the place is a protected site. Therefore, other surrounding bushes should be protected in order to preserve species from local extinction.